Analysis on The Students’ Comprehension of The Material of The Human and Animal’s Musculoskeletal System Using YouTube Video and Zoom Cloud Meetings Application - Aisyiah, Pratiwi Nur; Sujana, Atep; Sopandi, Wahyu (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
Human and animal’s musculoskeletal system is part of science that is included in the curriculum of the 5th Grade of Elementary School. This lesson requires a visual approach, either posters or a 3D anatomy kit, to describe the anatomy of the human and animal's musculoskeletal system such as bones of skeleton, muscles, and joints. COVID-19 pandemic has affected countries all over the world including Indonesia. Thus, since the beginning of 2020, this pandemic has shifted the student's learning method from the face-to-face meeting into the distance learning method by using supporting applications such as Whatsapp, Google Classroom, Zoom Cloud Meetings, and YouTube. Participated by 36 students of SD Bianglala consisting of two groups, this research was using a qualitative descriptive method. The instrument was using an essay test of 10 questions; each question represented a material comprehension indicator. The data processing technique was determining indicators of comprehension, scoring each question, categorizing the level of comprehension based on the indicators of each question, as well as analysis, and conclusions. The study results showed that the students' comprehension of the materials, including the most important part of the musculoskeletal system which allows motion, steps on how to keep the bones healthy, diseases that affect organs or organ abnormalities, animal's mobility organs, as well as their joints and muscle functions, was suggestively very well. It's showed in numbers 1, 4, 5, 6, 7, 9, and 10. While their comprehension of the function of human bones, parts of the bones based on their category, their names as well as their types, the motion directions, and the example of joints within the human's musculoskeletal system was rather well. It's showed in numbers 2, 3, and 8.